MANAJEMEN BIMBINGAN DAN KONSELING DI SMA - Su’ainah Su’ainah; Aliman Aliman; Osa Juarsa (Manajer Pendididikan, 2017)
The objective of this research is to describe the Management of Guidance and Counseling at Senior High School number 1 Kepahiang. The method is used descriptive qualitative, the data was taken by doing an interview, observation, and documentations. The results of the research shows that: (a) the planning of guidance and Counseling to plan a variety of services which will be given to the students for the right target, (b) The organizing of guidance and Counseling is started by making the organization’s structure that aims for the counselors guidance at the implementation’s stage will know on their duty, (c) the implementating of guidance and Counseling is done based on the program, but there are some problems that cause the program can not implemented well, (d) the controlling of guuidance and Counseling is done by the principle, (e) evaluating is done to know the success of the implementation of the planned program.